2009
DOI: 10.1121/1.3139899
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic profiles of distinct emotional expressions in laughter

Abstract: Although listeners are able to decode the underlying emotions embedded in acoustical laughter sounds, little is known about the acoustical cues that differentiate between the emotions. This study investigated the acoustical correlates of laughter expressing four different emotions: joy, tickling, taunting, and schadenfreude. Analysis of 43 acoustic parameters showed that the four emotions could be accurately discriminated on the basis of a small parameter set. Vowel quality contributed only minimally to emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 46 publications
4
50
0
4
Order By: Relevance
“…The outcomes of our annotation are mostly in line with previous findings ( [1,17,19]). During exhalation phases, if we exclude silences that are extremely frequent inside laughs, we obtained a large number of h-like phones (h, x, H, è), and voiced parts are mainly central vowels (@, 5, 8, 0).…”
Section: Laughter Phonetic Descriptionsupporting
confidence: 80%
See 1 more Smart Citation
“…The outcomes of our annotation are mostly in line with previous findings ( [1,17,19]). During exhalation phases, if we exclude silences that are extremely frequent inside laughs, we obtained a large number of h-like phones (h, x, H, è), and voiced parts are mainly central vowels (@, 5, 8, 0).…”
Section: Laughter Phonetic Descriptionsupporting
confidence: 80%
“…During the last decades, it received growing attention from researchers. If we still do not understand exactly why we laugh, progress has been made in understanding what it brings us (enhanced mood, reduction of stress, and other health outcomes [2,14]) and in describing how we laugh (see [1,5,17,19]). This paper will focus on the last aspect, laughter description, with the aim of improving automatic laughter processing.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…For example, both in speech (Scherer et al, 1991;Banse and Scherer, 1996;Johnstone and Scherer, 2000) and non-speech vocalisations (Szameitat et al, 2009(Szameitat et al, , 2011Sauter et al, 2010), anger, fear, and joy have all been associated with increased pitch. However, despite these commonalities, different emotional states are typically associates with distinct overall patterns (Patel et al, 2011), that is, distinct combinations of features.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these commonalities, different emotional states are typically associates with distinct overall patterns (Patel et al, 2011), that is, distinct combinations of features. For example, anger has been associated with increased pitch and loudness; fear with increased pitch and speech rate; joy with increased pitch, loudness, and speech rate; sadness with decreased pitch, speech rate, and loudness (Scherer et al, 1991;Banse and Scherer, 1996;Johnstone and Scherer, 2000;Szameitat et al, 2009Szameitat et al, , 2011Sauter et al, 2010). The resulting unique vocal profile helps to differentiate the affective quality of the vocalisation, and respond with the appropriate behaviour (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have directly examined relationships between specific acoustic properties and perceptual judgments. There is evidence that relationships between acoustic features and emotional judgments are similar across laughter and speech (Szameitat et al, 2009). found that voiced laughs (i.e., containing tonal information) were judged as being friendlier and more positive, compared to unvoiced laughs.…”
Section: Introductionmentioning
confidence: 99%